Sistem Persuratan Digital dalam Mendukung Pelayanan Administrasi Pemerintah di Desa Kalinanas Kabupaten Blora - Ahmad Setya Fany; Agung Kuswantoro (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
Correspondence services at the village level are still largely done manually, resulting in slow submission processes, inefficient archive management, and requiring residents to come directly to the village office. This study aims to develop a website-based digital correspondence system to support government administration services in Kalinanas Village, Japah District, Blora Regency. The method used is Research and Development (R&D) with the ADDIE model, which includes: analysis, design, development, implementation, and evaluation. Data were collected through observation, interviews, documentation, and questionnaires. System testing was conducted using black-box testing and user feasibility testing on 12 village officials. The results showed that the system was successfully developed and can be used for letter submission, data verification, archive management, and online letter status monitoring. The results of black-box testing showed that all main functions ran according to design, while the user feasibility test obtained an average score of 88.25% with a very feasible category. In conclusion, the developed website-based digital correspondence system has proven to be feasible and effective in supporting government administration services in Kalinanas Village. This system can simplify the letter management process and increase the efficiency of village administration services. As a follow-up, it is recommended that village officials undergo ongoing training and develop additional features to improve accessibility and user convenience.